Colour vision in group of subjects with and without chromagen filter - Veselý, P; Patočková, L; Hanák, L; Beneš, P (Ceska a slovenska oftalmologie, 2017)
Our aim in this study was to prove influence of chromagen filter on color vision quality. Further we wanted to compare quality of color vision in groups of young healthy persons with persons with maculopathy. In our study we had in total 39 subjects. First group contained 13 subjects with average age 23 years without important eye pathology. In the second group we had 13 patients (average age 68 years) with maculopathy. Third group contained subjects with average age 64 years without important eye pathology. While examination we used sorting tests for color vision: Farnsworth-Munsell test and Lanthony test. Results were evaluated according the Vingryse and King-Smith technique. We found that average total error score (TES) in young healthy subjects with color chromagen filter doesnt differ from TES value gained from patients with disease of macula (p = 0.86). Further we found that chromagen filter changes color vision in group of young subjects on statistical significant level (p = 0.01). But in clinical view this is not important color vision defect (TES = 107.46 and CI = 1.42). Next study result showed statistically not important difference between the color vision in young healthy patient (average age 23 years) and older healthy patients with average age 64 years (p = 0.58). Finally we can conclude that green color chromagen filter doesnt have negative influence for dyslectic patients who will use this filter all day. Further we proved that color vision deterioration of patients with macular disease is not important for practical distinguishing of colors but is important clinically for diagnostic purposes. Last but not least we brought result which shows not important difference between young healthy subjects and older subjects (23 versus 64 years).Key words: Color vision, chromagen lens, total error score, maculopathy.
Keywords: mladý dospělý; Adult; Color Perception Tests; poruchy barevného vidění; Young Adult; Color Vision; testy barvocitu; dospělí; Macula Lutea; vidění barevné; Aged; Color; macula lutea; barva; Humans; lidé; Color Vision Defects; senioři